APPROPRIATENESS OF TIMING OF INITIAL ANTIBIOTIC PRESCRIPTION AND ITS IMPACT ON SEPSIS PATIENT OUTCOMES IN THE ICU AT NABLUS GOVERNMENTAL HOSPITALS: A RETROSPECTIVE STUDY - Aqqad, Sarah (An-Najah National University, 2026)
Abstract Background: Sepsis is leading cause of mortality in intensive care units (ICUs), especially in low- and middle-income countries (LMICs). Administration of appropriate antibiotics promptly is a cornerstone of sepsis management; neverthless evidence regarding optimal timing is inconsistent, and most available data come from high-resource healthcare settings. This research evaluated the association between initial antibiotic timing and in-hospital mortality among ICU patients with sepsis in Nablus, Palestine. Additional objectives included describing patient characteristics, comorbidity patterns, sources of infection, reasons for delayed antibiotic initiation, and determining factors linked to mortality; these analyses were further categorized by the severity of sepsis. Methods: This retrospective study examined adult patients (≥18 years) with sepsis/septic shock from January 2023 to June 2025 admitted to the Internal Medicine ICU at Al-Watani Hospital Nablus, Palestine. Information regarding demographics, comorbid conditions, sepsis intensity, source of infection, timing of antibiotics, and outcomes during hospitalization was gathered from electronic medical records. Door-to-antibiotic time was classified as ≤1 hour, 1–3 hours, or >3 hours from the identification of sepsis. The primary outcome of this study was the occurrence of in-hospital mortality. An independent predictor of mortality included risk factors identified by multiple variable logistic regression analyses. Results: In a study of 297 ICU patients, antibiotics were started within ≤1 hour of sepsis identification for 44.8%, between 1–3 hours for 35.7%, and after >3 hours for 19.5%. Timely antibiotic treatment, administered either within 1 hour (adjusted odds ratio [aOR] = 1.45; 95% CI: 0.81–2.62) or within 3 hours (aOR = 0.78; 95% CI: 0.38–1.57), was not independently linked to mortality. In contrast, septic shock and a greater burden of comorbidities were independent predictors of mortality. Subgroup analyses consistently showed greater mortality in septic shock patients across all timing categories. Conclusions: In this ICU cohort with limited resources, the timing of early antibiotic treatment had no independent effect on mortality. The main factors influence outcomes were patient severity and the burden of comorbidities, highlighting the importance of tailored sepsis management and enhanced antimicrobial stewardship in Palestinian ICUs.
مدى ملاءمة توقيت وصف المضاد الحيوي الأولي وتأثيره على نتائج مرضى الإنتان في وحدات العناية المركزة في المستشفيات الحكومية بنابلس: دراسة استعادية